Analisis Motivasi Terhadap Hasil Belajar Mata Kuliah Bola Basket - Sutriawan, Agus agus; Syafruddin, Muhammad Akbar; Hasanuddin, M. Imran (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
This research is a type of quantitative research. This research aims to determine the effect of motivation on the learning outcomes of basketball courses for students of the Physical Education, Health and Recreation Study Program at FIK UNM. The sample in this study amounted to 37 people who were determined using purposive sampling technique. Data collection techniques for learning outcomes are taken from the final results of students' basketball courses. Meanwhile, data collection on motivation variables was carried out using a questionnaire using a Likert sample. The data analysis technique is carried out using a simple regression test which first goes through a prerequisite test consisting of a normality test and a linearity test. The results of data analysis obtained a Sig value. equal to 0.000 or <0.05, which shows that the motivation variable influences the learning outcomes of the basketball course, with an influence proportion of 61%. The conclusion of this research is that motivation has a significant influence on students' learning outcomes in basketball courses